Homologous Elements hs3a and hs3b in the 3′ Regulatory Region of the Murine Immunoglobulin Heavy Chain (Igh) Locus Are Both Dispensable for Class-switch Recombination - Yan, Yi (American Society for Biochemistry and Molecular Biology, 2011)
Immunoglobulin heavy chain (IgH) genes are formed, tested, and modified to yield diverse, specific, and high affinity antibody responses to antigen. The processes involved must be regulated, however, to avoid unintended damage to chromosomes. The 3′ regulatory region of the Igh locus plays a major role in regulating class-switch recombination (CSR), the process by which antibody effector functions are modified during an immune response. Loss of all known enhancer-like elements in this region dramatically impairs CSR, but individual element deletions have no effect on this process. In the present study, we explored the hypothesis that an underlying functional redundancy in the homologous elements hs3a and hs3b was masking the importance of either element to CSR. Several transgenic mouse lines were generated, each carrying a bacterial artificial chromosome transgene that mimicked Igh locus structure but in which hs3a was missing and hs3b was flanked by loxP sites. Matings to Cyclization Recombination Enzyme-expressing mice established “pairs” of lines that differed only in the presence or absence of hs3b. Remarkably, CSR remained robust in the absence of both hs3a and hs3b, suggesting that the remaining two elements of the 3′ regulatory region, hs1.2 and hs4, although individually dispensable for CSR, are, together, sufficient to support CSR.